Case of femoral diaphyseal stress fracture after long-term risedronate administration diagnosed by iliac bone biopsy - Nagai T; Sakamoto K; Ishikawa K; Saito E; Kuroda T; Inagaki K (Dove Medical Press, 2013)
Takashi Nagai, Keizo Sakamoto, Koji Ishikawa, Emi Saito, Takuma Kuroda, Katsunori Inagaki Department of Orthopaedic Surgery, Showa University School of Medicine, Shinagwa-ku, Tokyo, Japan Abstract: Bisphosphonate excessively inhibits bone resorption and results in pathological fracture of the femur or ilium. The subject of this study was administered risedronate for 7 years; we suspected an easy fracture of the femoral diaphysis. In this study, we report the results of this patient's bone biopsy and bone morphometric analysis. A 76-year-old female patient presented with right femoral pain. Bone mineral density of the anteroposterior surface of the 2nd to 4th lumbar vertebrae (L2-L4) was decreased and levels of bone turnover markers were high. Therefore, we initiated treatment with risedronate. As she continued the medication, urinary levels of cross-linked N-terminal telopeptides of type I collagen and alkaline phosphatase (bone-type isozyme) were found to be within the normal ranges. After 7 years of administration, the patient experienced pain when she put weight on the right femur and right femoral pain while walking. Plain radiographic examination revealed polypoid stress fracture-like lesions on the right femoral diaphysis and on the slightly distal-lateral cortical bone. Similar lesions were observed on magnetic resonance imaging and bone scintigraphy. We suspected severely suppressed bone turnover. Bone biopsy was obtained after labeling with tetracycline, and bone morphometric analysis was performed. On microscopic examination, slight double tetracycline labeling was observed. The trabeculae were narrow, and the numbers of osteoblasts and osteoclasts were decreased. Further, rates of bone calcification and bone formation were slow. Hence, we diagnosed fracture as a result of low turnover osteopathy. Risedronate was withdrawn, and Vitamin D3 was administered to improve the bone turnover. At 6 months, abnormal signals on magnetic resonance imaging had decreased and her pain while walking or undergoing the stress test disappeared as well. Thus, long-term administration of bisphosphonates may lead to easy fracture, although bone turnover markers were observed to be within the normal range. During bisphosphonate administration, physicians need to monitor closely and treat their patients for any pain experienced in the femoral region while walking or undergoing a stress test. Keywords: bisphosphonate, severely suppressed bone turnover, risedronate